(untitled) (Interapia – Journal of Clinic, Culture and Mental Sciences, 2025)
Abstract The article examines psychoanalysis as a tool for self-knowledge, emphasizing its importance in understanding the unconscious processes shaping human behavior. Drawing on Freud’s main works, it argues that psychoanalysis allows individuals to explore repressed emotions, inner conflicts, and behavioral patterns, fostering personal growth and emotional balance.